(untitled) (Research, Society and Development, 2022)
Objective: To analyze if the type of therapeutic support offered to individuals during the acute phase of COVID-19 will influence their performance on the 6-minute walk test during the post-COVID-19 phase. Methodology: This is a cross-sectional, descriptive study with a quantitative approach. It was carried out at the Laboratory of Kinesiotherapy and Manual Therapeutic Resources – LACIRTEM of the Federal University of Pernambuco (UFPE). Data collection occurred in the period from September 2020 to September 2021. The evaluation was divided into 2 stages, the first stage consisted of interviewing the participants for personal, sociodemographic, vital signs and information about the clinical history of the disease. Subsequently, functional capacity was assessed with the 6-minute walk test (6MWT). Results: 150 post-COVID-19 individuals were evaluated, 62% of which were female with a mean age of 49.28±12.59. The body mass index of the individuals was between the categories overweight and obesity grade I. Regarding the type of therapeutic support, it was observed that 58.7% of the individuals were in recovery at home. The type of therapeutic support had an influence on the performance of the 6MWT. Final Considerations: This study revealed the epidemiological profile of individuals who were part of the post-COVID-19 project at UFPE, in addition to showing the influence of therapeutic support on post-COVID-19 functional capacity. The data analyzed in the present study are important to better prevent and control the functional repercussions of COVID-19 survivors.